Diversion in the Investigation Process for Children in Conflict with the Law - Arianti Putri Purwanti; Mohammad Roesli; Bastianto Nugroho (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
Objectives of the Research to find out the framework of thought that underlies the implementation of Diversion in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System through Diversion. This research method uses normative juridical. What is meant by normative juridical research type is the research method carried out by focusing on positive legal norms in the form of statutory regulations. In this normative legal research, we will examine statutory regulations that will explain the appropriate form of diversion in resolving children's criminal cases in order to fulfill children's rights. Result Restorative Justice is a Diversion. If the child's case meets the requirements for diversion then the hope of restorative justice can be realized, namely by the success of diversion. Sometimes children's cases do not meet the requirements for diversion in accordance with the Law on the Juvenile Criminal Justice System, even though children's cases lead to restorative justice because the perpetrator and victim have received a fair solution by making peace and can recover as before. If the Diversion efforts are not completed, the child is threatened with punishment so this is not in accordance with the Principle of Deprivation of Freedom and Punishment as a last resort, because there are efforts that could have been carried out or attempted, namely Diversion, but were not carried out because there are restrictions on Diversion in Children's cases in accordance with Article 7 of the Law. -Law Concerning the Juvenile Criminal Justice System. If the Indonesian state does what the Philippine state does, namely applying diversion to every child case, then deprivation of liberty and punishment will truly be a last resort.